Pengaruh DPR, Firm Size Dan ROA Terhadap DER (Studi Pada Perusahaan Manufaktur Sektor Makanan dan Minuman yang Terdaftar di BEI Periode 2014-2018) - Mutia, Galuh Candra Setianing; Efriadi, Adi Rizfal (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
The Effect of Dividend Policy, Company Size and Profitability on Debt Policy in Food and Beverage Sector Companies Listed on the Indonesia Stock Exchange in the Period of 2014-2018. The purpose of this study was to determine the effect of the Dividend Policy, Company Size and Profitability on the Debt Policy in the food and beverage sector which is flat on the Indonesian stock exchange. The period used in this research is 5 years. This research design uses quantitative methods. The population of this research is the food and beverage sector manufacturing companies that have been and are still listed on the Indonesia Stock Exchange Period 2014-2018. Sampling techniques using purposive sampling and data obtained for research are 7 companies. The analytical method used is multiple linear regression. Based on the results of data analysis, Dividend Policy is not examined because the required data is incomplete and does not meet the requirements. The size of the company is mid-sized but not significant to the Debt Policy, with this Beta Unstandardized Coefficients value of 0.027 with a significance value of 0.146. Profitability has a negative and significant effect on the debt policy, with this Beta Unstandardized Coefficients value of -7,183 and a significance value of 0,000. KeyWord : Debt to Equity Ratio (DER), Dividend Payout Ratio (DPR) , Firmsize, and Profitability (ROA).